Perbedaan antara Video Asissted Thoracoscopy Surgery (VATS) dengan Torakotomi pada Non Small Cell Lung Cancer (NSCLC) : Sebuah Tinjauan Sistematik dan Meta Analisis - Putra, Fuad Iqbal Elka; Hanum, Hanifah (CV. Jasa Sukses Abadi, 2024)
Video-assisted thoracic surgery (VATS) lobectomy provides a minimally invasive approach for the management of early-stage lung cancer. This systematic review and meta-analysis is aim to provide the outcomes between VATS and thoracotomy lobectomy. The research is aim to compare between video-assisted thoracoscopis surgery and thoracotomy in non small cell lung cancer patient. Five articles databases were searched via PubMed. Primary outcomes were operative time, postoperative hospital stay, chest drainage volume, chest drainage time, and number of lymph node dissesction. Review Manager (RevMan) [computer program] version 5.4 was used to pool the data. There were significant results VATS has shorter postoperative length of stay (95% CI 1.08 to 4.83) and chest drainage volume (CI 25.83 to 344.98). There were not significant results in terms of operative time (95%CI -30.88 to 40.10), chest drainage time (95%CI -0.95 to 2.50), and number of lymph node rdissection (95%CI -0.67 to 1.740). VATS lobectomy is superior to thoracotomy lobectomy in terms of shorter postoperative length of stay (95% CI 1.08 to 4.83) and chest drainage volume (CI 25.83 to 344.98). The results also showed no significant differences between the two treatment modalities regarding the operative time, chest drainage time, and number of lymph nodes dissected.